Perinatal factors associated with amplitude-integrated electroencephalography abnormalities in preterm infants on the first day of life - Junia Sampel de Castro; Ana Teresa Figueiredo Stochero Leslie; Ruth Guinsburg (Elsevier, 2020)
Objective: Evaluate the association between perinatal factors and amplitude-integrated electroencephalogram abnormalities in preterm infants on the first day of life. Methods: This was a cross-sectional study of 60 infants with gestational age between 23 and 32 weeks, without malformations. Infants were continuously monitored by amplitude-integrated electroencephalogram on the first day of life, for at least 3 h. The tracings were recorded and analyzed in each column for the following: burst-suppression pattern, sleep-wake cycle, and amplitude of the lower margin (<3 μV or <5 μV). The association of maternal complications, mode of delivery, birth weight, gestational age, neonatal sex, resuscitation procedures, hypothermia on admission, and the Score for Neonatal Acute Physiology, Perinatal Extension, Version II [SNAPPE-II]) with amplitude-integrated electroencephalogram alterations was assessed by multiple logistic regression. Results: A discontinuous pattern occurred in 65% of infants, and a continuous pattern occurred in 23%. The burst-suppression pattern was associated with vaginal delivery (OR: 7.6; 95% CI: 1.1-53.1) and SNAPPE-II ≥ 40 (OR: 13.1; 95% CI: 1.8-95.1). A lower margin of the amplitude-integrated electroencephalogram of <3 μV was also associated with SNAPPE-II ≥ 40 (OR: 10.6, 95% CI: 2.3-49.2), while a value <5 μV was associated with lower GA (OR: 0.51, 95% CI: 0.34-0.76). There were no associations between the perinatal variables and the absence of a sleep-wake cycle in amplitude-integrated electroencephalogram recordings on the first day of life. Conclusion: Biological variables and clinical severity are associated with electroencephalographic characteristics of preterm infants on the first day of life and should be considered in clinical practice when amplitude-integrated electroencephalogram is performed. Resumo: Objetivo: Avaliar a associação entre fatores perinatais e anormalidades no eletroencefalograma de amplitude integrada em recém-nascidos prematuros no primeiro dia de vida. Métodos: Este é um estudo transversal de 60 bebês com idade gestacional entre 23-32 semanas, sem malformações. Os recém-nascidos foram continuamente monitorados por eletroencefalograma de amplitude integrada no primeiro dia de vida por pelo menos 3 horas. Os traçados foram registrados e analisados em cada coluna para: padrão de surto-supressão, ciclo de sono-vigília e amplitude da margem inferior (<3 μV ou <5 μV). A associação de complicações maternas, tipo de parto, peso ao nascer, idade gestacional, sexo do neonato, procedimentos de reanimação, hipotermia na admissão e Escore para Fisiologia Neonatal Aguda, Extensão Perinatal, versão II (SNAPPE-II) com alterações no eletroencefalograma de amplitude integrada foi avaliada por regressão logística múltipla. Resultados: Um padrão descontínuo ocorreu em 65% dos recém-nascidos e o padrão contínuo ocorreu em 23%. O padrão de surto-supressão foi associado ao parto vaginal (OR 7,6; IC95% 1,1-53,1) e SNAPPE-II ≥ 40 (OR 13,1; IC95% 1,8-95,1). Uma margem inferior do eletroencefalograma de amplitude integrada <3 μV também foi associada com escore SNAPPE-II ≥ 40 (OR 10,6, IC95% 2,3-49,2), enquanto um valor <5 μV foi associado com menor IG (OR 0,51, IC 95% 0,34-0,76). Não houve associações entre as variáveis perinatais e a ausência de ciclo sono-vigília nas gravações de eletroencefalograma de amplitude integrada no primeiro dia de vida. Conclusão: As variáveis biológicas e a gravidade clínica estão associadas às características eletroencefalográficas dos recém-nascidos prematuros no primeiro dia de vida e devem ser consideradas na prática clínica quando o eletroencefalograma de amplitude integrada é realizado.